Pengaruh Pijat Bayi terhadap Frekuensi dan Durasi Menyusu Bayi - Fitriahadi, Enny (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2016)
Background: Breast milk is the ideal source of nutrition with a balanced composition and adapted to the growing needs of the baby as well as the most perfect baby food, both quality and quantity. In Indonesia, the percentage of exclusive breastfeeding by the childs age and the characteristics of the respondent, the percentage of exclusive breastfeeding is higher in infants given only until the age of 0-1 months (45%), aged 2-3 months (38.3%), and the age of 4-5 months (31%). Exclusive breastfeeding is also higher in rural areas than urban areas, the percentage is respectively 41.7% and 50%. Method: Experimental research methods (quasy experimental design) or experiments that the research activities carried out by giving trial or treatment. Sampling was done by sampling technique is purposive sampling with criteria infants in good health. This research method using quantitative design of the experimental method (quasy experimental design) or experiments that the research activities carried out by giving trial or treatment. Sampling was done by purposive sampling. The sample in this study amounted to 15 babies. Data analysis using Chi Square formula. Results: The findings indicate that the effect of infant massage on the frequency and duration of suckling p value of 0.03, which means there Ho rejected and Ha accepted. Conclusion: Advice for parents, so that parents who have babies always routine to perform infant massage at least 3 times a week so that the baby be increased nutrient intake and nutritional status of infants either. For society as a science and motivational materials to parents to always perform infant massage to parents who have babies so that the health and nutritional status of infants to be good.